Assessing the effectiveness of financial regulation in the English Football League: "The dog that didn't bark". Issue 7 (16th September 2019) - Evans, Richard; Walters, Geoff; Tacon, Richard
Abstract : Purpose: The purpose of this paper is to provide an assessment of the effectiveness of the Salary Cost Management Protocol, a form of financial regulation introduced by the English Football League in 2004 to improve the financial sustainability of professional football (i.e. soccer) clubs. Design/methodology/approach: The analytical approach is to assess the effect of the regulation from evidence of change in measures of the financial performance of clubs drawing on three criteria: profitability, liquidity and solvency. A unique database was created from the published financial statements and notes to the accounts of the clubs in the Tier 4 league (known since 2004 as League Two) from 1994 to 2014 to encapsulate the 10-year period before and after the regulation was introduced. To show trends in the data within the study period, the data are reported in graphical form. The statistical significance of change in both the slope and intercepts for trends between breaks of interest in the data is estimated by linear regression. Findings: The results show that financial regulation failed to significantly improve the profitability or the solvency of football clubs in League Two. Whilst the liquidity of the clubs improved in response to the introduction of the financial regulation, the results show this was only in the year in which the financial regulation was introduced. Research limitations/implications: The results extend theoretical debate on financial regulation in sports leagues by moving beyond the assumption that financial regulation is a "technical exercise" to provide an alternative way of thinking about financial regulation as a "legitimising exercise". Originality/value: This is the first study to assess the impact of financial regulation for football league clubs over a longitudinal period. It is also extends previous research in which only single aspects of the financial sustainability of football clubs, such as insolvency, have been considered.